A new proposal for a grout-tooth connection. (15th January 2022) - Alghrir, Yassin; Al-kroom, Hussein; Schmid, Volker
Highlights: The non-welding connection of polymer concrete has good strength characteristics. The failure mode in both the polymer concrete connections and the cementitious grout connection is similar. In all connections, the load has been transferred by bottle-shaped compression fields along the connection. Stress distribution along the connection reflects that the teeth of the connection do not contribute equally to the strength of the connection. Abstract: The paper deals with the strength characteristics of a grouted connection proposed for the shear transfer between steel elements or steel-to-concrete connections. The connection has been designed and tested at TU Berlin (Technische Universität Berlin) in the chair of Hybrid and Composite structures (Verbundstrukturen). Three types of grout have been used. The commercial names of the grout are BETEC180, COMPONO, and Sikadur-42; BETEC180 belongs to the family of high-performance cementitious grout, whereas COMPONO and Sikadur-42 relate to polymer concrete. The three brands are chosen as an example represents the behavior of such connection using cementitious grout and polymer concrete. Though the compressive strengths of all grouts are close, there are substantial differences in the tensile and shear capacity between the cementitious grout and the polymer concrete grout. To investigate the performance of the connection under shear, three tests for each material are conducted. The average load capacities of the three types of grout (BETEC, COMPONO, and Sikadur-42) are: 67, 7 kN, 117, 3 kN, and 124, 5 kN, respectively. Furthermore, the connection with cementitious grout showed the most brittle performance, and Sikadur-42 connection presents the best behavior in terms of ductility and load capacity. However, the failure mode is comparable in all connections. Three-dimensional nonlinear Finite Element Models (FEM's), for the three different connections, have been carried out using ANSYS software. The FEMs are in good agreement with the observations in the experiments. The models are useful in explaining the stress development and crack pattern within the grout and the failure mode of the connection.